Religious Shifts in Tarogong Kidul: Life in the Social Media Age - Sukmawati, Desi; Muhtadi, Asep S.; Wibisono, M. Yusuf (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2025)
This research investigates the transformation of religious behavior in the community of Tarogong Kidul, Garut Regency, within the rapidly evolving landscape of social media. Framed through a sociological-anthropological lens and guided by Pierre Bourdieu’s theory of habitus, the study applies a qualitative descriptive method using a case study approach. Data were gathered through in-depth interviews, participatory observations, and document analysis, with triangulation employed to ensure validity. The analysis reveals a significant shift in religious expression—from deeply internalized spiritual practices to symbolic and commodified forms—driven by factors such as technological advancement, urbanization, and socioeconomic change. Social media platforms like WhatsApp, Facebook, and YouTube have emerged as influential arenas for da’wah and religious engagement, yet they also contribute to the fragmentation of traditional religious authority and the marketization of faith. Although public participation in routine religious activities appears to decline, adaptive religious centers like the Grand Mosque of Garut demonstrate increased relevance and engagement. At the same time, the cultural fabric of Sundanese Islam faces challenges from unfiltered global content, often rendering communities passive consumers. However, improvements in education and income empower individuals to reinterpret religious values within modern, urban realities. This study concludes that what occurs in Tarogong Kidul is not a break from tradition, but a dynamic negotiation between inherited religious habitus and new social structures of the digital age. The research offers theoretical insight into the interplay between tradition and modernity, methodological contributions through a robust qualitative design, and practical value for designing inclusive, media-sensitive religious outreach strategies in contemporary urban societies.